Smart Agency Management System (SAMS) / Norbaiti Tukiman … [et al.] - Tukiman, Norbaiti; Sahudin, Zahariah; Abdullah, Hasni; Mohd. Saad, Nurul Huda (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Insurance industry plays an important role in generating growth to the nation's economy. Basically, established insurance company incorporated many subsidiary company called agencies to expand their business. The agencies consist of agents and insurance clients. However, the agencies faced problem in managing their agents and clients in fast, systematic and effective way. Hence Smart Agency Management System is a comprehensive management web based system, which help agency to manage their agents and clients information and monitor their businesses. The system consists of two modules, new agent registration module and agency management module. The methodology used in developing this system is Rational Unified Process (RUP) with Unified Modelling Language (UML) Model which is an object-oriented modelling method. This system was developed in Active Server Pages (ASP) environment using Java Script. Hopefully the system will give benefit to the insurance agencies in increasing their business performance and toward paperless management